معهد الحكمة لتحفيظ القرآن الكريم والابداعات - محمد بابن غدا; غزالي محمد (Prosiding Konferensi Nasional Bahasa Arab, 2021)
Praise and thanks be to God almighty who sent down the Noble Qur’an in a clear and genuine Arabic language, may Allah’s blessings and peace be upon the prophet who as a mercy to the whole world. The Arabic language is the most eloquent language, it has the most beautiful expressions, it is the best of the languages in coordinating phrases, and it has the best words for clarifying data (BAYAN), and it is a means of acquaintance between tribes and peoples and linking relations. Indeed, teaching the noble Qur’an is like teaching the Arabic language, and preserving the noble Qur’an is like preserving the Arabic Language, this article will talk about the new inventions applied in teaching the noble Qur’an during covid 19 pandemic in Indonesia:Key words: Quran, teaching Arabic language.